The Anti-Sickling and Oxidative Properties of Ethanol Leaf Extract of Ocimum gratissimum L. (Scent Leaf) - Onwubiko U. I.; Imo C.; Onwubiko G. N.; Dawoye Y.; Rayyanu S. S.; Solomon J. E. (Darul Yasin Al Sys, 2026)
This study evaluated the anti-sickling potential of the ethanol leaf extract of Ocimum gratissimum using microscopy-based assays. The extract markedly reversed 2% sodium metabisulfite–induced sickled red blood cells to normal biconcave forms, and microscopic observations indicated that the percentage reversal of sickled cells was both concentration- and time-dependent. At 250 μg/mL, the percentage reversal of sickled cells at 0, 20, and 30 minutes was 77.00%, 72.31%, and 71.77%, respectively, whereas the control (absence of extract) showed no reversal. At 500 μg/mL, the corresponding reversals were 76.19%, 69.60%, and 74.00%, while at 1000 μg/mL they were 71.49%, 75.92%, and 87.70%, respectively, demonstrating enhanced anti-sickling activity at higher extract concentrations over time. UV–Visible spectrophotometric analysis of oxyhaemoglobin revealed a gradual increase in the 630 nm band, consistent with the oxidation of ferrous (Fe²⁺) oxyhaemoglobin to ferric (Fe³⁺) methaemoglobin; the absorbance peak at 650 nm, attributable to chlorophyll, was clearly distinguishable from the haemoglobin oxidation band at 630 nm. In addition, the ethanol leaf extract of O. gratissimum exhibited a stabilizing effect on erythrocyte haemolysis. Phytochemical analysis showed the presence of aromatic and alkylic compounds, which may contribute to intracellular anti-sickling activity by interfering with haemoglobin S polymerization and, through their hydrophobic properties, may also modulate the erythrocyte lipid bilayer membrane.